Các nhân tố ảnh hưởng đến sự sẵn lòng tiêu dùng sản phẩm xanh: Trường hợp xăng sinh học E5 - Bạch Ngọc Hoàng , Ánh; Cao Quốc , Việt; Hà Minh , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Based on rational action theory, environmental stimulus and price perception theory, and the debate between previous research results, this study examines the impact of green skepticism, subjective environmental knowledge, environmental concern, price consciousness, and environmental apathy on customers’ willingness to buy green (the product is E5 biofuel). The study used quantitative analysis methods on a survey of 539 consumers in Ho Chi Minh City to evaluate the scale and test the model using the SEM analysis method. The findings confirm that green skepticism and environmental apathy negatively impact the willingness to consume E5 biofuels, and environmental concern has a positive impact. In particular, green skepticism has the most significant influence, and environmental concern has the most negligible influence. The study proposes several measures to promote consumers’ willingness to buy green goods in general and the willingness to use E5 biofuel in Ho Chi Minh City.
Keywords: Price consciousness; Green skepticism; Environmental concern; Environmental apathy; Subjective environmental knowledge; Willingness to use E5 biofuels